A study on distribution of assets and liabilities upon separation of non-muslim cohabitants in Malaysia / Nurul Asyiqin Shukri...[et al.] - Shukri, Nurul Asyiqin; Nani, Nur Farhana; Ramli, Nur Fatin Afiqah (Faculty of Law, 2012)
Despite fast changing ways of life, the modern living arrangement namely 'cohabitation' has been hesitantly recognised either by the society or law in Malaysia. Most researchers and scholars believe that though the society welcomes technological changes in their lives, in the case of family ties, most people stick to the traditionally accepted way of bringing up a family, which is a legally registered marriage. However, it must be noted that the number of people who practice cohabitation in Malaysia has been increasing over the years and like other relationships, some are meant to last forever and some end up halfway for various reasons. The lack of legal recognition of cohabitation has caused problems particularly in the division of assets and financial rights. As cohabitants are also part of the society, it would be necessary for the state to look into this matter and assist them in any possible way. Therefore, this research looks into the problems faced by cohabitants post their relationship and examine whether the law provides them with any form of protection.. This research also compares the situation in other countries such as Scotland, India, United States and others in relation to the division of assets and liabilities post cohabitation. It also proposes recommendations to assist the cohabitants in facing their problems.